Peran Media Sosial dalam Mempengaruhi Perilaku Gizi Remaja SMPN X Depok - Nourmayansa Vidya Anggraini; Serri Hutahaean; Nayla Kamilia Fithri; Vionita Apriliana; Talita Alifa Salsabila (Malahayati Nursing Journal, 2023)
ABSTRACT Adolescence is a period of transition from childhood to adulthood. Changes that occur in adolescents tend to cause various problems and changes in behavior in adolescent life. The total population of adolescents aged 10-19 years is 1.2 billion or 16% of the world's population. Teenagers are at risk of being overweight. Teenagers use social media a lot. If teenagers explore nutritional information from social media, it will increase their knowledge about nutrition.This study aims to identify the role of social media in influencing adolescent nutrition. This research was conducted at SMPN X Depok in July 2022 to 261 students in grades 7, 8, 9 using simple random sampling technique. Data collection techniques were carried out by taking data through questionnaires. Univariate data analysis aims to provide a description of the characteristics of respondents and research variables. Bivariate analysis was conducted to determine the relationship between mass media and nutritional behavior in adolescents at SMPN X Depok. After analyzing the relationship between the role of mass media and adolescent nutritional behavior, the p value = 0.005 (p 0.05) which means that there is a significant relationship between mass media and adolescent nutritional behavior. Mass media plays an important role in adolescent nutritional behavior. Parents should monitor the use of mass media by teenagers so that positive things are taken by teenagers in their use. Keywords: Nutrition, Mass Media, Obesity, Youth  ABSTRAK Masa remaja merupakan masa peralihan dari masa kanak-kanak menuju dewasa. Perubahan yang terjadi pada remaja cenderung menyebabkan berbagai permasalahan dan perubahan perilaku pada kehidupan remaja. Jumlah populasi remaja usia 10-19 tahun sebanyak 1.2 milyar atau 16% dari populasi dunia. Remaja memiliki risiko kelebihan berat badan. Remaja banyak menggunakan sosial media. Apabila remaja mengeksplor informasi gizi dari sosial media maka akan meningkatkan pengetahuan remaja berkaitan dengan gizi. Pada penelitian ini bertujuan mengidentifikasi peran media sosial dalam memberikan pengaruh terhadap gizi remaja. Penelitian ini dilakukan di SMPN X Depok pada bulan Juli 2022 terhadap siswa kelas 7, 8, 9 sebanyak 261 siswa dengan menggunakan teknik simple random sampling. Teknik pengumpulan data dilakukan dengan mengambil data melalui penyebaran kuesioner. Analisa data univariat bertujuan dalam memberikan deskripsi karakteristik responden dan variabel penelitian. Analisis bivariate dilakukan untuk mengetahui hubungan antara media massa dengan perilaku gizi pada remaja SMPN X Depok. Setelah dilakukan analisis tentang hubungan peran media massa dengan perilaku gizi remaja didapatkan nilai p value = 0.005 (p 0.05) yang memiliki arti bahwa terdapat hubungan bermakna antara media massa dengan perilaku gizi remaja. Media massa memberikan peranan penting dalam perilaku gizi remaja. Orang tua sudah seharusnya melakukan pemantauan dalam penggunaan media massa oleh remaja supaya hal positif diambil remaja dalam penggunaannya. Kata Kunci: Gizi, Media Massa, Obesitas, Remaja